Preparation of Porous Hydroxyethyl Cellulose Materials to Utilize Lactic Acid with Vacuum-Assisted Process - Haeun Lee; Do Chun Nam Kung; Sang Wook Kang (Molecules, 2023)
For the first time, we succeeded in manufacturing a 2-hydroxyethyl cellulose (HEC)-based composite membrane with improved thermal stability, for use as a battery separator, coating a HEC polymer solution to a polypropylene (PP) support and using a vacuum-assisted process. A HEC polymer solution was prepared by utilizing HEC and lactic acid (LA) as a plasticizer. A vacuum-assisted process was used to move ethanol, which a mobile phase to permeate a plasticized region in the HEC polymer side for pore formation. The pores formed with uniform nano sizes, and areas in which some large pores formed were observed. The thermal stability of the composites was measured using TGA. The thermal decomposition temperatures were measured at about 250 °C for the neat HEC, about 210 °C for the HEC/LA film, and about 335 °C for the HEC/LA/PP membrane before the process. After the vacuum-assisted process, the first and second thermal decomposition were observed at about 360 °C and 450 °C, respectively. The HEC/LA/PP membrane after the process showed greater thermal stability than before the process. This means that the adhesion between the HEC polymer and the PP support was created through the rearrangement of the HEC chain, as LA escaped after the process, and it was seen indirectly that the mechanical strength was enhanced. In particular, the surface of the membrane was observed by SEM to investigate whether the HEC penetrated into the PP to block its pores, and whether the HEC region collapsed. Furthermore, the interaction of the HEC chain with the additives and the rearrangement of the HEC was confirmed using FT-IR. As a result, we demonstrated that the mechanical strength and thermal stability of the manufactured HEC/LA/PP membrane were enhanced.